Community natural resource management in the highlands of Ethiopia - Gebremedhin, Berhanu; Pender, J.L.; Tesfay, G. (International Food Policy Research Institute, 2002)
This paper evaluates the nature and determinants of community management (collective action) of woodlots and grazing lands in the northern Ethiopian highlands of Tigray. It identifies the nature of management of woodlots and grazing lands, the roles of different organisations (local and external) in managing them, and the benefits and problems encountered. Econometric analysis was used to investigate the determinants of collective action and its effectiveness in managing these resources. The paper ends with comment from Ephraim Nkonya.